DENTAL HEALTHCARES SYSTEM DURING THE COVID-19 PANDEMIC AND IMPACT OF DIGITAL TECHNOLOGIES - Ioana Martu; Oana-Elena Ciurcanu; Carmen Nicoleta Savin; Diana Diaconu-Popa; Oana Butnaru; Liliana Pasarin (Romanian Society of Oral Rehabilitation, 2023)
The present study aims to analyze the impact of these modern methods of treatment on the current activity of dentists and their influence on the addressability of patients in dental offices during the pandemic. In the COVID-19 pandemic context, the addressability to the dental offices decreased. These digital technologies represent the future of dentistry and are essential, especially during this period. In this sense, a survey was done by distributing a questionnaire to 114 dentists with private practices in Iasi. Our questionnaire included specific items to objectively analyze the practitioners' knowledge, their attitude towards the current use of digital technologies, and the impact of these methods on their activity. The answers clearly show that dentists are interested in implementing digital systems, allowing prosthetic work to be performed in a shorter time and with maximum accuracy, reducing materials consumption and the risk of contamination for patients and the dental team. Minimizing treatment time is favorable and excludes complications leading to optimal treatment results by simplifying the entire procedure.These systems allow the obtaining of optimal functional and aesthetic prosthetic constructions.